Metabolomic profiling of developing perilla leaves reveals the best harvest time - Chen, Jiabao; Guo, Long; Yang, Guiya; Yang, Aitong; Zheng, Yuguang; Wang, Lei (Frontiers in Plant Science, 2022)
The objective of this study was to investigate the variation in nutritional compositions and phytochemical substances of Perilla frutescens (L.) Britt at different harvest times. Changes in their contents were reported through seven different harvest times during three months. Ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS) and gas chromatography-mass spectrometry (GC-MS) were applied to analyze metabolites in perilla leaves (PLs) during its developmental process. In total, 118 metabolites were identified, including volatile and non-volatile compounds, such as terpenoids, sugars, amino acids, organic acids, fatty acids, phenolic acids, flavonoids, and others. Principal component analysis (PCA) indicated great variations of metabolites during PLs development. Clustering analysis (CA) clarified the dynamic patterns of the metabolites. The heatmap of CA showed that most of the detected metabolites were significantly accumulated at stage 4 which is the pre anthesis period, and declined afterwards. The results of the present study provide a comprehensive overview of the metabolic dynamics of developing PLs which suggested that pre anthesis period is the best harvest time for PLs.